2014
DOI: 10.17116/stomat201493625-31
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key markers of normal and pathogenic microbiota determining health of periodontium by NGS-sequencing 16S-rDNA libraries of periodontal swabs

Abstract: By using NGS-sequencing libraries of DNA from periodontal swabs with primers specific to V6 region of 16S rDNA prevalence of bacterial genera and species in periodontal microbiota of patients with aggressive periodontitis and healthy donors was analyzed. Six genera of putative periodontal protectors and eight periodontal pathogens were identified with respect to aggressive (but not chronic) periodontitis. Statistically relevant over-colonization by general Porphyromonas, Treponema, Synergistes, Tannerella, Fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the same way, Corynebacterium appeared to be more associated with healthy subgingival biofilm (32,33). Moreover, Rothia and Corynebacterium were among the bacteria that showed the greatest increases after periodontal treatment (34), while a study suggested that Corynebacterium might be considered a putative periodontal protector (35). Veillonella and Actinomyces have been negatively correlated with clinical markers in CP (36), and Neisseria was found in inactive sites (25).…”
Section: Discussionmentioning
confidence: 93%
“…In the same way, Corynebacterium appeared to be more associated with healthy subgingival biofilm (32,33). Moreover, Rothia and Corynebacterium were among the bacteria that showed the greatest increases after periodontal treatment (34), while a study suggested that Corynebacterium might be considered a putative periodontal protector (35). Veillonella and Actinomyces have been negatively correlated with clinical markers in CP (36), and Neisseria was found in inactive sites (25).…”
Section: Discussionmentioning
confidence: 93%
“…Bergeyella , Lautropia , Rothia , Propionibacterium and Cardiobacterium were more abundant in the healthy participants. Bergeyella was considered as putative periodontal protectors in periodontal swabs from the participants ( Zorina et al., 2014 ). Lautropia mirabilis , Propionibacterium propionicum , Rothia dentocariosa/mucilagenosa and Cardiobacterium hominis were significantly more prevalent in the healthy group than in the periodontitis patients ( Colombo et al., 2009 ; Ikeda et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%